Circular RNA circ-TNPO3 suppresses metastasis of GC by acting as a protein decoy for IGF2BP3 to regulate the expression of MYC and SNAIL - Ting Yu; Lingyu Ran; Hongwen Zhao; Pin Yin; Wei Li; Jie Lin; Hui Mao; Dongping Cai; Qiang Ma; Xiaojuan Pan; Xiaolin Wang; Jingjing Wu; et al. (Elsevier, 2021)
Gastric cancer (GC) continues to be the most common gastrointestinal malignancy in China, and tumor metastases are a major reason for poor prognosis. Circular RNAs (circRNAs) are an intriguing type of noncoding RNAs with important regulatory roles. However, the roles of circRNAs in GC metastasis have not been fully elucidated. Here, we reported that circ-transportin 3 (TNPO3) was significantly downregulated in 103 pairs of GC tissues compared with matched noncancerous tissues. The level of circ-TNPO3 expression correlated with differentiation of GC, and plasma circ-TNPO3 could serve as a potential diagnostic biomarker. Functionally, circ-TNPO3 inhibited proliferation and migration of GC in vitro and in vivo. We further verified that circ-TNPO3 competitively interacted with insulin-like growth factor 2 binding protein 3 (IGF2BP3) protein; thus, the role of IGF2BP3 in stabilizing MYC mRNA was weakened, which inhibited the expression of MYC and its target SNAIL. Taken together, circ-TNPO3 acts as a protein decoy for IGF2BP3 to regulate the MYC-SNAIL axis, thereby suppressing the proliferation and metastasis of GC. Therefore, circ-TNPO3 has the potential to serve as a therapeutic target for GC.